Dél-Dunántúli települések egy országos piackutatás tükrében (Settlements of South Transdanubia in the Light of a National Market Survey) - Zoltán Koltai (DETUROPE)
We made a layered questionnaire survey in 2004-2005. We wanted to find the answer to the following questions: What aspects do Hungarian citizens prefer when choosing their place of residence? What characteristics, advantages and disadvantages do they use to describe the settlement types of different size? Which Hungarian settlements are considered competitive by the respondents and why? Which are the settlements that the stakeholders see as real centres of gravity? How much are the respondents willing to move to another settlement? In the light of the results, we repeated our survey of the population in 2012-2013, allowing thereby the comprehensive evaluation of a period of almost ten years. In this phase of data recording we used the method of a layered questionnaire survey again, in which it was one thousand private persons again who responded to our questions.